A Mini-Review of The Typical Wastewater Treatment Technologies - Wahid Ali Hamood Altowayti,; Chan Mei Ting,; Norzila Othman,; Zubaidah Md Saleh,; Faris Ali Hamood AL-Towayti,; Abdullah Faisal Alshalif,; Shafinaz Shahir, (Progress in Engineering Application and Technology, 2022)
Many studies have been carried out in recent years to increase the efficacy of wastewater treatment methods. High population expansion, on the other hand, has resulted in increased consumerism, pollution, and resource demands. As a result, it appears that evaluating typical wastewater treatment procedures in order to choose the most efficient one is required. Several technologies, including precipitation, membrane technology, and adsorption approaches, have been employed to meet the required discharge standards. During the adsorption process, electrostatic attraction and repulsion between molecules drive the interaction between the adsorbate and adsorbent. As a result, the adsorption method may be employed in a variety of wastewater treatment applications to remove contaminants via a binding interaction between molecules. In this work, the most applied technologies for treating wastewater around the world have been reviewed.